Ferruccio Busoni postcard photograph with autograph quotation from Beethoven's Variations for piano, WoO 80 - Busoni, Ferruccio, 1866-1924:::Creator::::::::::::
Undated postcard photograph of Ferruccio Busoni accompanied by Busoni's handwritten quotation of the first two measure of the theme of the Variations for piano in C minor, WoO 80, by Beethoven, with Busoni's inscription "Bravissimo! 8 July 1897 in Berlin" followed by his signature.